Anisotropic Cellular Network Formation in Engineered Muscle Tissue through the Self‐Organization of Neurons and Endothelial Cells. Issue 3 (21st August 2014) - Takahashi, Hironobu; Shimizu, Tatsuya; Nakayama, Masamichi; Yamato, Masayuki; Okano, Teruo
<x xml:space="preserve">Abstract</x> Tissue anisotropy directed by cell sheets: Aligned myoblasts can be harvested as an anisotropic cell sheet using a micropatterned thermoresponsive substrate. Neurons and endothelial cells sandwiched between multiple anisotropic cell sheets self‐organize oriented cellular networks in the tissue construct. This simple tissue engineering technique is useful for the creation of biomimetic microstructures in complex tissue, required for future advances in regenerative medicine. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>